Obtención de un insecticida biológico a partir de la higuerrilla(Ricinus Communis), Machala 2014. - Ramos Jaramillo, Elvis German (2015)
This project aims to determine the incidence of parasites in children of early age and to detect what are the factors that allow its appearance in the body thereof.